An Analysis of the Relationship between Socio-Economic Status of Parental Involvement and Child Social Emotional Learning in Karachi, Pakistan - Kiran, Kanwal (2023)
Parental involvement and a child’s social-emotional learning (SEL) are vital factors in a child's holistic development. This study emphasizes the essential role of parental involvement in children's SEL development in Pakistan, highlighting the need for context-sensitive approaches. It explores the critical, yet under-explored, link between Pakistani parental involvement and the social and emotional development of children aged 5-10 years. It also examines how disparities in socioeconomic backgrounds affect parents' priorities for their children's SEL. There is a significant gap in understanding how Pakistani parents contribute to their children's SEL growth. Hence the objectives of this study are to provide a comprehensive overview of how Pakistani parental involvement affects their children's SEL, and how socioeconomic background influences the priorities Pakistani parents assign to different aspects of children's SEL. A mixed-method research design was employed, integrating quantitative and qualitative data to provide a comprehensive view of how parental involvement affects SEL outcomes. Key findings reveal significant socioeconomic disparities between the Orangi and Southern districts of Karachi, influencing parental involvement. Hypothesis testing yielded the results that Pakistani parents from higher socioeconomic backgrounds have a broader understanding of SEL, encompassing a wider range of skills such as emotional regulation, empathy, and self-advocacy compared to parents from lower socioeconomic backgrounds. Regarding the influence of SES and culture, limited access to resources and chronic stress associated with low SES might hinder Pakistani parents' ability to provide consistent and responsive support for their children's social-emotional needs. However, in Karachi the Orangi district parents were found to be responsive and involved despite their lower SES. Lastly, Pakistani parents often prioritize social skills like cooperation and respect for authority, reflecting the collectivist nature of Pakistani culture, especially in lower SES areas. These findings emphasize the need for context-sensitive approaches to provide effective support.